2021
DOI: 10.3346/jkms.2021.36.e168
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Validity of the Arabic Version of the Stress and Anxiety to Viral Epidemics-6 Items (SAVE-6) Scale among the General Population in Lebanon

Abstract: This study explored the psychometric properties of the Arabic version of the Stress and Anxiety to Viral Epidemics-6 items (SAVE-6) scale for assessing people's anxiety in response to the viral epidemic in Lebanon. The 406 participants responded voluntarily to the online survey that included the SAVE-6, Generalized Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire-9 (PHQ-9) tools. The single-structure SAVE-6 model showed good internal consistency (Cronbach's α = 0.773). The SAVE-6 scale also showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 8 publications
8
30
0
1
Order By: Relevance
“…In this study, a single-structure model of SAVE-6 was confirmed to be valid and in line with previous studies ( 8 , 9 ). However, we observed a relatively low factor loading value of 0.446 for item 1, “Are you afraid that the virus outbreak will continue indefinitely?” The survey was conducted during the summer of 2020, when people were worried that the COVID-19 pandemic would be difficult to control, which may have contributed to the high proportion of answers of “often” (53.8%) and “always” (17.0%) among medical students.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, a single-structure model of SAVE-6 was confirmed to be valid and in line with previous studies ( 8 , 9 ). However, we observed a relatively low factor loading value of 0.446 for item 1, “Are you afraid that the virus outbreak will continue indefinitely?” The survey was conducted during the summer of 2020, when people were worried that the COVID-19 pandemic would be difficult to control, which may have contributed to the high proportion of answers of “often” (53.8%) and “always” (17.0%) among medical students.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, a single-structure model of SAVE-6 was confirmed to be valid and in line with previous studies (8,9). However, we observed a relatively low factor loading value of 0.446 for item 1, "Are you afraid that the virus outbreak will continue indefinitely?"…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations